2016
DOI: 10.3389/fnana.2016.00112
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Reliability of Quantitative and Weighted T1 and T2∗ Mapping for Myelin-Based Cortical Parcellation at 7 Tesla

Abstract: Different magnetic resonance (MR) parameters, such as R1 (=1/T1) or T2∗, have been used to visualize non-invasively the myelin distribution across the cortical sheet. Myelin contrast is consistently enhanced in the primary sensory and some higher order cortical areas (such as MT or the cingulate cortex), which renders it suitable for subject-specific anatomical cortical parcellation. However, no systematic comparison has been performed between the previously proposed MR parameters, i.e., the longitudinal and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 45 publications
8
63
0
Order By: Relevance
“…Recent studies in humans and nonhuman primates have demonstrated the value of T1-based MR imaging for visualizing the myeloarchitecture of the cortex. [23][24][25] Among the different T1 MR imaging techniques, magnetization prepared 2 rapid acquisition gradient echoes (MP2RAGE) provides the best tissue contrast at high spatial resolution while minimizing field inhomogeneities that affect other techniques at 7T. 26,27 We achieved high resolution while preserving image quality by combining multiple repetitions of the same 3D MP2RAGE acquisition.…”
mentioning
confidence: 99%
“…Recent studies in humans and nonhuman primates have demonstrated the value of T1-based MR imaging for visualizing the myeloarchitecture of the cortex. [23][24][25] Among the different T1 MR imaging techniques, magnetization prepared 2 rapid acquisition gradient echoes (MP2RAGE) provides the best tissue contrast at high spatial resolution while minimizing field inhomogeneities that affect other techniques at 7T. 26,27 We achieved high resolution while preserving image quality by combining multiple repetitions of the same 3D MP2RAGE acquisition.…”
mentioning
confidence: 99%
“…That is, the variation of T 1 values across the cortex is remarkably low after normalB1+ correction. For a comparison of the intersubject and scan–rescan COV with that of other (quantitative) contrasts (e.g., T 2 *), we refer the reader to Haast et al (2016). The reduction of the superior‐to‐inferior gradient of low‐to‐high T 1 —that led to the initially high COV across regions—resulted in a cortical T 1 distribution that is more comparable with previous studies at lower field strengths and are less affected by normalB1+ effects, revealing the typical myelin‐related cortical pattern (Glasser & Van Essen, 2011; Lutti, Dick, Sereno, & Weiskopf, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the Sa2RAGE, the parameters were: TR/TE = 2,400/0.78 ms, TD 1 /TD 2  = 58/1,800 ms, α 1 /α 2  = 4°/11°, and GRAPPA factor = 2 in PE direction (anterior–posterior) with 24 references lines. See Haast, Ivanov, Formisano, and Uludag (2016) for further details on other scanning parameters. The TR‐FOCI inversion pulse (Hurley et al, 2010) and dielectric pads containing a 25% suspension of barium titanate in deuterated water, placed around the head proximal to the temporal lobe areas (Teeuwisse et al, 2012), were used to improve normalB1+ homogeneity across the brain and locally, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative T1 (qT1) relaxometry data was acquired using a 3D-MP2RAGE sequence (0.8mm isotropic voxels, 240 sagittal slices, TR=5000ms, TE=2.9ms, TI 1=940ms, T1 2=2830ms, flip angle 1=4°, flip angle 2=5°, iPAT=3, bandwidth=270 Hz/px, echo spacing=7.2ms, partial Fourier=6/8). We combined two inversion images for qT1 mapping in order to minimise sensitivity to B1 inhomogeneities and optimize intra-and intersubject reliability (74,75).…”
Section: Replication In Independent Samplementioning
confidence: 99%